High-risk chronic lymphocytic leukemia in the era of pathway inhibitors: integrating molecular and cellular therapies - Dreger, Peter (Blood, 2018)
Visual Abstract - Download figureOpen in new tabDownload powerpoint - - High-risk chronic lymphocytic leukemia (CLL) has been defined by clinical and/or genetic resistance (TP53 abnormalities) to treatment with chemoimmunotherapy (CIT). With the availability of pathway inhibitors (PIs), such as kinase inhibitors and BCL2 antagonists, the outlook of CIT-resistant patients has dramatically improved. Here, we propose a revision of the concept of high-risk CLL, driven by TP53 abnormalities and response to treatment with PI. CLL high-risk-I, CIT-resistant is defined by clinically CIT-resistant disease with TP53 aberrations, but fully responsive to PI. This category is largely the domain of PI-based therapy, and cellular therapy (ie, allogeneic hematopoietic cell transplantation) remains an option only in selected patients with low individual procedure-related risk. In CLL high-risk-II, CIT- and PI-resistant, characterized by increasing exhaustion of pharmacological treatment possibilities, cellular therapies (including chimeric antigen receptor-engineered T cells) should be considered in patients eligible for these procedures. Moreover, molecular and cellular therapies are not mutually exclusive and could be used synergistically to exploit their full potential.